2013
DOI: 10.21859/isv.7.1.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Foot-and-Mouth Disease Virus by Real Time Reverse Transcription Polymerase Chain Reaction Assay in Iran

Abstract: Background and Aims: Accurate and rapid diagnosis is necessary for effective control and prevention of foot-and-mouth disease (FMD). In present study, was evaluated real time reverse transcription-polymerase chain reaction (rRT-PCR) assay along with diagnostic routine methods for the detection of all seven serotypes of FMD virus (FMDV), namely O, C, A, SAT1, 2, 3 and Asia 1 in biological samples at the reference laboratory for FMD, Iran. Materials and Methods: Two different RT-PCR assays targeting two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…The current study revealed that both tests used in this study were extremely efficient for diagnosing FMD in cattle, and Advances in Animal and Veterinary Sciences January 2020 | Volume 8 | Issue 1 | Page 7 concurs with the results of Ahmadi et al (2013) and Al-Rodhan and Salem (2014). For the first time four genotypes of FMDV (A, O, Asia-1 and SAT genotypes) were identified in Nineveh province, Iraq with detection rate of 12.39%, 6.95%, 17.39% and 3.69% respectively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The current study revealed that both tests used in this study were extremely efficient for diagnosing FMD in cattle, and Advances in Animal and Veterinary Sciences January 2020 | Volume 8 | Issue 1 | Page 7 concurs with the results of Ahmadi et al (2013) and Al-Rodhan and Salem (2014). For the first time four genotypes of FMDV (A, O, Asia-1 and SAT genotypes) were identified in Nineveh province, Iraq with detection rate of 12.39%, 6.95%, 17.39% and 3.69% respectively.…”
Section: Discussionsupporting
confidence: 83%
“…The seroprevalence of FMD in Middle and South of Iraq was 61.42% using FMD 3ABC Bo Ov ELI-SA test (Abood et al, 2009). Also, Ahmadi et al (2013) who indicated that the occurrences of FMD in Iran were 91.3% and 90.7% using antigen ELISA test and conventional RT-PCR technique respectively. The prevalence in cattle in all Iraqi provinces was 68.7% (Al-Salihi, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation